Impact of antibiotic withdrawal and starvation conditions on plasmid elimination and consequent loss of resistance - Hiba Akram; Shaniyaal Shahid; Hina Bukhari; Qurat-Ul-Ain; Khadeja Iqbal; Muhammad Asif (Journal of the Pakistan Medical Association, 2022)
Objective This study was designed to study resistance loss due to plasmid elimination under experimental conditions including withdrawal of antibiotics and administration of starvation conditions. Methodology This experimental study was conducted at Department of Pathology, King Edward Medical University, Lahore, from September 2019 to December 2019. A single sensitive clinical isolate of Escherichia coli, showing resistance towards ampicillin was collected and separately sub-cultured in three different culture broths: tryptic soya broth, minimal broth and control broth for a period of one month under standard laboratory conditions. Minimum inhibitory concentrations of the strains were calculated after every 7 days to check antibiotic susceptibility. Results MIC value of the initial strain of E.coli measured on Day 1 was 6mg/mL and it became sensitive after continual sub-culturing in the absence of antibiotics in 21 days. Due to starvation conditions the bacterial strain exhibited sensitivity to an even lower antibiotic conc. of 1.5mg/mL on the 28th day. Bacterial growth inhibition zones determined by disc diffusion method using an ampicillin disc of 10µg/mL showed no zone of inhibition. Conclusion In the absence of triggering factors such as antibiotics allow the bacteria to negatively select against the defensive traits exhibiting an onset of gradual loss of resistance over a period of time. Also the unavailability of sufficient nutrients for standard bacterial growth and survival further amplifies the rate of plasmid elimination and the consequent loss of resistance. Key-words: Antibiotic resistance, Plasmid elimination, Antibiotic withdrawal, Resistance loss, Starvation conditions.